Tetranuclear Copper(I) Iodide Complexes: A New Class of X-ray Phosphors - Kirakci, Kaplan; Fejfarová, Karla; Martinčík, Jiří; Nikl, Martin; Lang, Kamil (Inorganic chemistry, 2017)
We report intensive visible light radioluminescence upon X-ray irradiation of archetypal tetranuclear copper(I) iodide complexes containing triphenylphosphine or pyridine ligands in the solid state. These properties, attractive for the design of X-ray responsive materials, can be attributed to the heavy Cu4I4 cubane-like core, the absence of oxygen quenching of the emissive triplet states, and the high photoluminescence quantum yields. Radioluminescence originates from the same emissive triplet states as those produced by ultraviolet excitation as confirmed by the observed radioluminescence thermochromism. The radioluminescence properties are also preserved after incorporation of these complexes into polystyrene films, making them appealing for the development of plastic scintillators.